Expression of the novel hepatitis C virus Core+1/ARF protein in the context of JFH1-based replicons - Kotta-Loizou, Ioly; Bartenschlager, Ralf (Journal of virology, 2015)
Hepatitis C virus contains a second open reading frame within the core gene, designated core+1/ARF. Here we demonstrate for the first time expression of core+1/ARF protein in the context of a bicistronic JFH1-based replicon and report the production of two isoforms, core+1/L (long) and core+1/S (short), with different kinetics.